Peningkatkan Kesejahteraan Psikologi Pasien Kanker pada Akhir Kehidupan dengan Intervensi Dignity Therapy - Erni Saraswati; Yati Afiyanti; Dewi Gayatri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to improve the psychological well-being of cancer patients at the end of life with dignity therapy interventions. The research method used is a systematic review. The search used six databases: Science Direct, Proquest, Clinicalkey Nursing, Springerlink, Scopus, and Pubmed. From the specified keywords End of life, dignity therapy, improving psychological well-being, impact of dignity therapy, and effect of dignity therapy, data was obtained for 1,313 articles. The research results showed that in seven reviewed journals, dignity therapy was proven to be effective in reducing anxiety distress and improving psychological well-being in advanced cancer patients. In conclusion, dignity therapy can be used as an option in providing patient care at the end of life to enhance the psychological well-being of patients and families. Keywords: Dignity Therapy, Cancer, Psychological Welfare